Antimalarial and Anticancer Activity Evaluation of Bridged Ozonides, Aminoperoxides, and Tetraoxanes. (21st September 2022) - Coghi, Paolo; Yaremenko, Ivan A.; Prommana, Parichat; Wu, Jia Ning; Zhang, Rui Long; Ng, Jerome P. L.; Belyakova, Yulia Yu.; Law, Betty Yuen Kwan; Radulov, Peter S.; Uthaipibull, Chairat; Wong, Vincent Kam Wai; Terent'ev, Alexander O.
Abstract: Bridged aminoperoxides, for the first time, were investigated for the in vitro antimalarial activity against the chloroquine‐resistant Plasmodium falciparum strain K1 and for their cytotoxic activities against immortalized human normal liver (LO2) and lung (BEAS‐2B) cell lines as well as human liver (HepG2) and lung (A549) cancer cell lines. Aminoperoxides exhibit good cytotoxicity against lung A549 cancer cell line. Synthetic ozonides were shown to have high activity against the chloroquine‐resistant P. falciparum . A cyclic voltammetry study of peroxides was performed, and most of the compounds did not show a direct correlation in oxidative capacity‐activity. Peroxides were analyzed for ROS production to understand their mechanism of action. However, none of the compounds has an impact on ROS generation, suggesting that ozonides induce apoptosis in HepG2 cells through ROS ‐ independent dysfunction pathway. Abstract : Bridged aminoperoxides exhibit good activity and selectivity toward the A549 lung cancer cell line. Bridged ozonides demonstrate high antimalarial activity in vitro and selectivity against the chloroquine‐resistant P. falciparum strain K1. Ozonides induce apoptosis in HepG2 cells through a reactive oxygen species (ROS)‐independent dysfunction pathway.